The structure study of low-temperature rhombohedral bismuth oxide-based electrolytes - Morrison, Caitlin Audrey (University of the Witwatersrand, Johannesburg, 2025)
Solid oxide fuel cells (SOFCS) are high-temperature devices, that operate from 800 to 1000 °C. In this work, stabilized bismuth oxide (Bi2O3) is investigated as a potential solid electrolyte for SOFCs. When doping Bi2O3 with suitable metals, an unnatural phase known as the rhombohedral phase can form at intermediate temperatures between 450 and 650 °C. The overall aim of this study was to investigate the formation and conductive properties of the rhombohedral phase of doped Bi2O3. The dopants included lanthanum (La), samarium (Sm) and gadolinium (Gd) at concentrations between 15 mol and 25 mol%. The citric sol-gel method was used for synthesis of materials that were characterized using laboratory and synchrotron powder X-ray diffraction, Raman spectroscopy and Electrochemical impedance spectroscopy. Substitution of Bi2O3 with 25 mol% La, Sm or Gd confirmed that all three substituents predominantly formed the rhombohedral phase at this concentration. However, La has distinct conductive behaviour compared to the other two substituents with a significant conductivity jump at 700 °C. Varying the substituent concentration in Bi(1−𝑥)Sm𝑥O1.5 from 15 to 25 mol% revealed that the least substituted material had the highest conductivity, but was not stable and underwent a phase change at 550 °C. Annealing duration of Bi0.75Sm0.25O1.5 was varied between 5 and 15 hours at 750 °C, which revealed that the time-length of annealing does not have a significant influence on phase or conductivity behaviour. Annealing this same material at two different temperatures, 610 °C and 750 °C, formed different phase compositions at room temperature and had different conductive behaviour. This work provides further insight on how to leverage synthetic and structural conditions to successfully form the rhombohedral phase and improve its conductive behaviour.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2025
Keywords: Rhombohedral bismuth oxide phase; Solid oxide electrolyte; X-ray diffraction; Oxide conductivity; Electrochemical impedance spectroscopy; Bismuth oxide; Sol-gel synthesis; Rare earth metal dopants; Raman spectroscopy; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-4: Quality education